The Role of PPKn Teachers in Increasing Students' Reading Interest in PPKn Subjects at SMP Negeri 1 Gorontalo - Ni Ketut Nuriati; Rasid Yunus; Ariyanto Nggilu (Universitas Muhammadiyah Palu, 2025)
This study aims to find out students' reading interest in PPKn subjects at Junior High School 1 Gorontalo City, to find out the role of PPKn teachers in increasing students' reading interest in PPKn subjects at Junior High School 1 Gorontalo. The results of the study show that the role of PPKn teachers in increasing students' reading interest in PPKn subjects at SMP Negeri 1 Gorontalo, namely teachers play an active role in guiding students and role models in building a literacy culture in schools, especially students' interest in reading. The reading interest of students at SMP Negeri 1 Gorontalo is still finding many problems, especially in terms of the interest of the students themselves, because in this day and age everything is all modern, especially in terms of books they can access books not only through the library but also online. So most of them if they want to read, most of them are online, but some, most still have no interest in reading, especially since libraries have begun to be rare and can be counted, in one class there are only a few people, not up to 10 people.